PENERAPAN RASIO KEUANGAN SEBAGAI ALAT UKUR KINERJA PERUSAHAAN - Agus Muqorobin; Moechamad Nasir (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2009)
This research analyzed the performance of finance of KUD South Banyudono which is relied on by financial statement of KUD period 2002-2006. As for this research target to know the finance efficiency of KUD South Banyudono tend to go up or descend and to analyze the finance performance of KUD South Banyudono during last five year, evaluated from ratioanalysis finance covering ratio liquidity, leverage and profitability. The result of research indicate thatthe fund management of KUD South Banyudono havefulfilled the efficient criterion seen from its finance ratio analysis during period 2002, 2003, 2004, 2005, 2006 and finance performance of KUD South Banyudono evaluated from ratio analysis its finance have good enough Pursuant to analyzed the ratio that is liquidity, leverage, and profitability indicate that the finance performance of KUD South Banyudono not yet efficient, that is not yet owned the cash which liquid, too much debt, and ability print the low profit.